Procedural Sedation with Dexmedetomidine for Anterior Mediastinotomy in a High-Risk Patient - Miguel Pratas; Jorge Aires; Nuno Pereira da Silva; Tiago Oliveira; Cristovão Pinto; Jiele Li; Ana Filipa Ribeiro (Case Reports in Anesthesiology)
Perioperative management of patients with mediastinal masses still poses a challenge for the anesthesiologist, as the use of general anesthesia can be associated with acute perioperative cardiorespiratory impairment resulting from the mass collapsing on the airway or vascular structures. Dexmedetomidine can be used for procedural sedation due to its reversible sedative and anxiolytic properties with dose-dependent effects, while not interfering with ventilatory drive. These features are of particular interest for the perioperative management of patients with large anterior mediastinal masses. In this case, we report our anesthetic management of a 22-year-old male scheduled for anterior mediastinotomy, with a large anterior mediastinal mass, with 50% distal tracheal compression and marked collapse of the superior vena cava and brachiocephalic trunk. In the operation theatre, an infusion of dexmedetomidine was titrated to adequate anesthetic depth while keeping the patient under spontaneous ventilation with oxygen (O2) supplementation and local anesthetic infiltration of the surgical site. Mediastinotomy lasted for about 30 minutes, during which the patient maintained appropriate ventilation and hemodynamic stability. No adverse events occurred perioperatively. Diagnostic procedures such as mediastinotomy for tissue biopsy are necessary to achieve a histological diagnosis. High-risk patients may present with severe postural symptoms, stridor, cyanosis, and radiological evidence of more than 50% airway obstruction, tracheal compression with bronchial compression, pericardial effusion, or superior vena cava syndrome. Relaxation of bronchial smooth muscles under general anesthesia increases the risk of airway obstruction. In this case, with the use of dexmedetomidine combined with local anesthetic infiltration, spontaneous ventilation and muscle tone were preserved, decreasing the probability of intraoperative complications. It is our opinion that dexmedetomidine combined with local anesthetic infiltration can be a safe option for procedural sedation in patients presenting with high-risk anterior mediastinal masses for mediastinotomy.